Karakteristik mikroselulosa mikrokristalin dari rumput laut merah Eucheuma cottonii - Edison Edison; Andarini Diharmi; Ela Davera Sari (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Microcrystalline Cellulose (MCC) is a modified of cellulose widely used as an additive in food and pharmaceutical industry. MCC is used in the pharmaceutical field as an excipient compound in the manufacture of tablets. Raw materials for MCC are of high cellulose content, such as Eucheuma cottonii seaweed. This study was aimed to determine the characteristics of MCC from seaweed E. cottonii. The MCC was obtained by hydrolyzing of α-cellulose from seaweed E. cottonii using HCl solution with three different concentrations: 2, 2.5 and 3 N. The chemical compositions (water, ash, protein, lipid, and carbohydrate) of red seaweed flour were determined. The moisture, ash, sensory, yield, and pH of the MCC were also analysed. The results showed that E. cottonii seaweed flour had moisture, protein, fat, ash, and carbohydrate content 3.88%, 0.85%, 2.4%, 3.44%, and 89.4% respectively. HCl concentrations had a significant effect on the moisture and ash content. The MCC had a yield of 35.8-38.00%, pH 5.73-6.82, moisture content 4.09.6, ash 0.94-4.90%. The characteristics of the MCC was in accordance with the standards of the British Pharmacopeia except the ash content.